Games Are Social/Media(ted)/Technology Too . . . (29th April 2015) - O'Donnell, Casey; Consalvo, Mia
In this manifesto, we argue that social media research needs to take the broader field of game studies in the exploration and understanding of social media. Many of the results, theories, and concepts developed in the study of games has significant implications for the study of all social media. Of course, game studies should be paying attention to social media research too.